Applications of biotechnology in cardiovascular therapeutics - Jain, Kewal K.; SpringerLink (Online service). (Totowa, N.J. Humana Press, 2011)
For physicians, surgeons, and scientists working on cardiovascular disorders, Applications of Biotechnology in Cardiovascular Therapeutics serves as an invaluable reference by collecting the essential writings of Dr. Kewal K. Jain on the topics of biotechnology as they relate to cardiovascular disease. This thorough volume includes such subjects as biotechnology and therapeutic delivery to the cardiovascular system, cell-selective targeted drug delivery, cell and gene therapies, including antisense and RNA interference, cutting-edge gene therapy approaches, as well as personalized cardiology as a way of integrating new technologies into the selection of the best possible treatment for an individual patient. Selected references from recent literature are collected for each chapter, and the text is supplemented by a variety of useful tables and figures. Comprehensive and up-to-date, Applications of Biotechnology in Cardiovascular Therapeutics will be tremendously useful for those working in life sciences and the pharmaceutical sciences, and the inclusion of some basics of cardiovascular diseases will greatly benefit nonmedical readers as well.
Cardiovascular Therapeutics -- Drug Delivery to the Cardiovascular System -- Role of Nitric Oxide in Cardiovascular Disorders -- Biomarkers of Cardiovascular Disorders -- Molecular Diagnosis of Cardiovascular Disorders -- Nanobiotechnology in Cardiovascular Disorders -- Cell Therapy for Cardiovascular Disorders -- Gene Therapy for Cardiovascular Disorders -- Coronary Angioplasty & Drug-Eluting Stents -- Personalized Cardiology.
Keywords: Chemistry; Biotechnology; Chemistry; Biotechnology